Pulmonary Pharmacokinetic and Pharmacodynamic Evaluation of Ampicillin/Sulbactam Regimens for Pneumonia Caused by Various Bacteria, including Acinetobacter baumannii - Tetsushu Onita; Kazuro Ikawa; Noriyuki Ishihara; Hiroki Tamaki; Takahisa Yano; Kohji Naora; Norifumi Morikawa (MDPI AG, 2023)
This study aimed to assess the dosing regimens of ampicillin/sulbactam for pneumonia based on pulmonary pharmacokinetic (PK)/pharmacodynamic (PD) target attainment. Using the literature data, we developed pulmonary PK models and estimated the probabilities of attaining PK/PD targets in lung tissue. Against bacteria other than A. baumannii (the general treatment), the PK/PD target was set as both 50% time above the minimum inhibitory concentration (T > MIC) for ampicillin and 50% T > 0.5 MIC for sulbactam. For the A. baumannii treatment, the PK/PD target was set as 60% T > MIC for sulbactam. The pulmonary PK/PD breakpoint was defined as the highest minimum inhibitory concentration (MIC) at which the target attainment probability in the lung tissue was ≥90%. The lung tissue/serum area under the drug concentration-time curve from 0 to 3 h (AUC0-3h) ratios for ampicillin and sulbactam were 0.881 and 0.368, respectively. The ampicillin/sulbactam AUC0-3h ratio in the lung tissue was 3.89. For the general treatment, the pulmonary PK/PD breakpoint for ampicillin/sulbactam at 3 g four times daily in typical patients with creatinine clearance (CLcr) of 60 mL/min was 2 μg/mL, which covered the MIC90s (the MICs that inhibited the growth of 90% of the strains) of most gram-positive and gram-negative bacteria. For the A. baumannii treatment, the pulmonary PK/PD breakpoint for ampicillin/sulbactam at 9 g 4-h infusion three times daily (27 g/day) in patients with a CLcr of 60 mL/min was 4 μg/mL, which covered the MIC90 of A. baumannii. A PK/PD evaluation for pneumonia should be performed in the lung tissue (the target site) rather than in the blood because sulbactam concentrations are lower in lung tissue. These findings should facilitate the selection of ampicillin/sulbactam regimens for pneumonia caused by various bacteria, including A. baumannii.